PERENCANAAN PEMERINTAH KABUPATEN LINGGA DALAM PENGEMBANGAN DESTINASI PARIWISATA TAHUN 2017 - Aldi, Rian; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tourism is one of the development sectors that must receive the attention of local governments to continue to be developed. Because this sector is highly potential for development in the field of people’s economy and income from  non oil commodities. Tourism development planning is needed in the development of tourism destinations because it is assessed as an important step in determining the success of a work program to be implemented. Therefore, it takes accuracy in order to develop the planning of tourism development so that the objectives are directional and optimal. To provide a basic spirit a clear direction of purpose in the planning. It takes the principles in the preparation of the tourism development that is allocative, innovative, single and multi objectives, indicative and imperatives. This research aims to describe the government planning of Lingga Regency in developing tourism destinations. Then also to find out the optimal inhibitory factors of government planning of Lingga regency in the development of tourism destinations in 2017. The research site is conducts in Lingga Regency, precisely at the Office of the Youth Tourism department and Sports District of Lingga and in tourism destinations in the area. Further, data collection techniques are conducted with interview and documentation.The results of this research is the planning of the Government of Lingga Regency in the development of tourism destinations as an effort to improve the competitiveness of tourism sectors has not run optimally. It is caused by several factors that such as lack of quality human resource planners are largely untrained. Differences between government and community, and limited budget funds from local governments in support of tourism development programs.       Keywords : Allocative, Innovative, Single and Multi Objectives, Indicative and Imperative.